Detection of quasiperiodic oscillation in x-ray light curve of blazar OJ 287 using SWIFT/XRT - Khatiwada, Manil; Bhusal, Nabin; Khanal, Bishal; Rana, Karishma (Himalayan Physics, 2025)
Blazar OJ 287, a unique BL Lac object, exhibits rich variability across multiple wavelengths. This study investigates the possible presence of Quasiperiodic Oscillation (QPO) in the X-ray regime using archival data from the SWIFT/XRT telescope. The dataset comprises light curve observations from 2005 to 2022. By applying Power Spectral Density (PSD), phase folding, and epoch folding methods, we identify a consistent QPO at approximately 1.59 hours. To validate the significance of this detection against red noise, we performed statistical tests, including false alarm probability calculations and Monte Carlo simulations based on red noise models. The PSD spectrum shows a broad power-law decline consistent with red noise, but multiple distinct peaks in the high-frequency range (10-4-10-3) Hz exceed the 99.7% confidence level derived from 1,000 red noise simulations. These results confirm that the detected QPO features are unlikely to be due solely to stochastic variability. This strengthens the case for a genuine QPO signal, suggesting coherent physical processes, such as accretion disk instabilities or jet modulation near the central supermassive black hole. The detection provides valuable insight into the emission mechanisms of blazars and supports the presence of periodic activity in the inner regions of OJ 287.